2020
DOI: 10.1002/aisy.202000043
|View full text |Cite
|
Sign up to set email alerts
|

Smart Manufacturing for Smart Cities—Overview, Insights, and Future Directions

Abstract: According to statistics provided by the UN in 2018, the global urban population rose from 0.75 billion in 1950 to 4.2 billion by 2018, a 5.5-fold increase in nearly seven decades. Currently, this 4.2 billion urban population accounts for 55% of the current global population, and given the trend, the global urban population is expected to touch 68% of total population by 2050. [1,2] To keep abreast with this growing shift toward urbanization, the last decade witnessed a multitude of global projects across the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 127 publications
(213 reference statements)
1
20
0
Order By: Relevance
“…To take care of the unique complexities and coordination of the shop floor, ML was employed for process monitoring, quality control and system integration in the manufacturing environment [42]. The authors in Reference [42] captured several applications of ML to the smart factory namely for production, supply chain planning, health status or conditions of equipment. However, there is a growing need take note of the occupational health and safety of workers as argued by several human-centered researches for smart factory [40,41].…”
Section: Background On Machine Learning Algorithmsmentioning
confidence: 99%
“…To take care of the unique complexities and coordination of the shop floor, ML was employed for process monitoring, quality control and system integration in the manufacturing environment [42]. The authors in Reference [42] captured several applications of ML to the smart factory namely for production, supply chain planning, health status or conditions of equipment. However, there is a growing need take note of the occupational health and safety of workers as argued by several human-centered researches for smart factory [40,41].…”
Section: Background On Machine Learning Algorithmsmentioning
confidence: 99%
“…These include energy from renewable sources such as solar, etc. Smart manufacturing refers to adopting ICT for automation of all aspects in the manufacturing domain [39,40].…”
Section: Smart Living Environmentmentioning
confidence: 99%
“…Meanwhile, the words "world," "global," and "city" indicate that the transition to smart factories is a global trend, and that smart factories are being built as one of the policies for implementing smart cities. Suvarna et al [40] revealed that smart factories can become key drivers of smart cities by actualizing some key functions such as digital technology, smart citizenship, government initiatives, environment, health and safety, and urban planning.…”
Section: Semantic Analysis Finding 1: Issue Networkmentioning
confidence: 99%